Absorption and intermediary metabolism of purines and pyrimidines in lactating dairy cows. Issue 4 (26th January 2015) - Stentoft, Charlotte; Røjen, Betina Amdisen; Jensen, Søren Krogh; Kristensen, Niels B.; Vestergaard, Mogens; Larsen, Mogens
Abstract : About 20 % of ruminal microbial N in dairy cows derives from purines and pyrimidines; however, their intermediary metabolism and contribution to the overall N metabolism has sparsely been described. In the present study, the postprandial patterns of net portal-drained viscera (PDV) and hepatic metabolism were assessed to evaluate purine and pyrimidine N in dairy cows. Blood was sampled simultaneously from four veins with eight hourly samples from four multi-catheterised Holstein cows. Quantification of twenty purines and pyrimidines was performed with HPLC–MS/MS, and net fluxes were estimated across the PDV, hepatic tissue and total splanchnic tissue (TSP). Concentration differences between veins of fifteen purine and pyrimidine nucleosides (NS), bases (BS) and degradation products (DP) were different from zero ( P ≤ 0·05), resulting in the net PDV releases of purine NS (0·33–1·3 mmol/h), purine BS (0·0023–0·018 mmol/h), purine DP (7·0–7·8 mmol/h), pyrimidine NS (0·30–2·8 mmol/h) and pyrimidine DP (0·047–0·77 mmol/h). The hepatic removal of purine and pyrimidine was almost equivalent to the net PDV release, resulting in no net TSP release. One exception was uric acid (7·9 mmol/h) from which a large net TSP release originated from the degradation of purine NS and BS. A small net TSP release of the pyrimidine DP β-alanine and β-aminoisobutyric acid ( − 0·032 to 0·37 mmol/h) demonstrated an outlet of N into the circulating N pool. No effect of time relative to feeding was observed ( P >0·05). These data indicate that considerable amounts of N are lost in the dairy cow due to prominent intermediary degradation of purines, but that pyrimidine N is reusable to a larger extent.